Understanding talent flux - analysing job posts to understand economic activities - Beh, Wei Siang (2018)
In Singapore, several online job portals provide a service for interested job applicants by hosting employer posted job advertisements. Although users of these services could perform a job query with a keyword search and optional additional filters, the only statistic that they could access off the portal was the total sum of applicable search results from the query. As various invaluable data could be extracted off information provided by the job posts, the lack in data analysis and visualization tools limits the potential of resources provided by online job portals.